Dynamic Hybrid Topology Design for Integrated Traffic Support in WDM Mesh Networks - Youssef, Mina; Choi, Baek-Young; Scoglio, Caterina M.; Park, Eun Kyo (My University, 2010)
The future Internet will require the transport of a wide range of services including high bandwidth one-to-many applications, with a dynamic interconnection of devices. WDM layer support realizes such services in a transparent, reliable and efficient way. Most of the recent studies have been focused on efficiently building and configuring light-paths for unicast or light-trees for multicast in isolation, and do not take existing traffic demands and configuration into consideration. In this paper we consider a dynamic design problem of integrated traffic in a realistic WDM mesh network. In such a network, new traffic demands of either multicast and/or unicast are supported dynamically in the presence of an existing mixture of traffic. The amount of bandwidth per wavelength is abundant, while the wavelengths and light splitting capabilities on WDM switches are limited. Using subwavelength sharing among traffic demands of unicast and multicast, we build a hybrid virtual topology that exploits both existing light-trees and light-paths. By optimizing WDM resources in addition to resource sharing with existing unicast and multicast demands, we truly maximize the WDM layer capability and efficiently support more traffic demands. We validate the efficiency of our approach with extensive simulations on various network topologies.
Keywords: WDM networks; Dynamic topology design; Unicast; Multicast